First evidence of rock wall permafrost in the Pyrenees (Vignemale peak, 3, 298 m a.s.l., 42°46′16″N/0°08′33″W). (1st September 2021) - Rico, Ibai; Magnin, Florence; López Moreno, Juan Ignacio; Serrano, Enrique; Alonso‐González, Esteban; Revuelto, Jesús; Hughes‐Allen, Lara; Gómez‐Lende, Manuel
Abstract: Permafrost is a relevant component of the Pyrenean high mountains, triggering a wide range of geomorphological cryogenic processes. Although in the past decades there has been an increase in frozen ground studies in the Pyrenees, there are no specific studies about rock wall permafrost, its presence, distribution, thermal regime, or historical evolution. This work combines measured rock surface temperatures (RSTs, from August 2013 to April 2016) along an elevation profile (four sites) on the north facing the rock wall of the Vignemale peak (3, 298 m a.s.l., 42°46′16″N/0°08′33″W) and temperature modeling (CryoGRID2) to determine the presence of permafrost and to analyze its evolution since the mid‐20th century. Simulations are run with various RST forcings and bedrock properties to account for forcing data uncertainty and varying degrees of rock fracturing. Results reveal that warm permafrost may have existed down to 2, 600 m a.s.l. until the early 1980s and that warm permafrost is currently found at 2, 800 m a.s.l. and up to 3, 000 m a.s.l. Cold (<−2°C) permafrost may exist above 3, 100–3, 200 m a.s.l. Systematic investigations on rock wall permafrost must be conducted to refine those results in the Pyrenees. The elevation shift in warm permafrost suggests an imminent disappearance of permafrost in the Vignemale peak.